Highly efficient catalytic pyrolysis of polyethylene waste to derive fuel products by novel polyoxometalate/kaolin composites. Issue 6 (June 2020) - Attique, Saira; Batool, Madeeha; Yaqub, Mustansara; Goerke, Oliver; Gregory, Duncan H.; Shah, Asma Tufail
We report here alumina-substituted Keggin tungstoborate/kaolin clay composite materials (KAB/kaolin) as polyethylene cracking catalysts. KAB/kaolin composites with varying concentrations of KAB (10–50 wt.%) were synthesized by the wet impregnation method and successfully characterized by Fourier-transform infrared spectroscopy, powder X-ray diffraction, thermo-gravimetric analysis and scanning electron microscopy with energy dispersive X-ray spectroscopy analytical techniques. Use of KAB loaded kaolin composites as the catalyst for low-density polyethylene (LDPE) cracking exhibited a higher percentage of polymer conversion (99%), producing 84 wt.% of fuel oil and negligible amount (˂ 1 wt.%) of solid residue while thermal cracking produced ~22 wt.% residue. Furthermore, gas chromatography–mass spectrometry analysis of oil obtained by non-catalytic cracking exhibited a high selectivity to high molecular weight hydrocarbons (C13 –C23 ) compared to the catalytic cracking where 70 mol.% of gasoline range hydrocarbons (C5 –C12 ) were produced. We propose that higher cracking ability of our prepared catalysts might ensue from both Brønsted and Lewis acid sites (from KAB and kaolin respectively), which enhanced the yield of liquid fuel products and reduced the cracking temperature of LDPE. These findings suggest that the prepared composites were cost-effective and excellent cracking catalysts that could be recommended for highly efficient conversion of waste plastic materials to petrochemicals at an industrial scale.